Pengaruh Pemanfaatan Media Sosial Instagram Sebagai Sarana Promosi Untuk Meningkatkan Minat Beli di Café Yamoke Makale Kabupaten Tana Toraja - Arisusanti Madao; Jens Batara Marewa; Astriwati Biringkanae (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to determine the effect of promotions on increasing sales volume at Waroeng Sablon Tana Toraja printing. The type of research used in this research is quantitative descriptive. The number of samples used in this research was 35 Waroeng Sablon customers. Data was collected using a questionnaire. This research uses simple linear regression analysis with the SPSS for Windows version 26 application. The results of this research show that the promotion variable has a positive and significant effect on capital structure. The coefficient of determination shows a result of 0.024. This means that the ability of the independent variable, namely promotion, to influence the dependent variable, namely sales volume, is 2.4%, while the other 97.6% is influenced or explained by other factors that are not included in the variables examined in this research